ANALISIS DIAMETER PIPA PDAM SEBAGAI JALUR TRANSMISI SINYAL WI-FI PADA FREKUENSI 2.4 GHZ - Susanti H. Hasan; Yono Hadi Pramono (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Have performed the analysis of metal pipe PDAM as transmission line wave had Wi-Fi at a frequency of 2.4 GHz. The method of attenuation measurements with observations on a variety of pipe diameters. The setting is done by using an access point as a Wi-Fi transmitter through monopole antenna. So also on the type of receiver used monopole antenna. To optimize Wi-Fi radiation in order to fully enter into the pipe, then use the box as a Faraday cage conductor who will wrap up a second access point both at the transmitter and receiver. From the analysis of the pipe diameter PDAM to a diameter of 3 inches (7.65 cm) loss / attenuation of 13.61 dBm, to a diameter of 4 inches (10.16 cm) loss / attenuation of 13.02 dBm, and for a diameter of 6 inches (15.24 cm) loss / attenuation of 1.66 dBm. Compared with without using the pipe as a transmission line for the same distance of 3 meters loss / attenuation reaches 56.1 dBm. Overall results of this study will be useful for people to get a Wi-Fi signal communication via pipeline PDAM. Keyword : Wi-Fi, Monopole Antenna, Wave Transmission, Attenuation.